The Effectiveness of a Proposed Program Based on The Theory of Brain-Based Learning in Developing Systemic Thinking Among Seventh Grade Students in Biology - Ashqi Suleman Haso; Afrah Yassin Muhammad (Zanco Journal of Humanity Sciences)
The aim of the present study is to identify the effectiveness of a proposed program according to the theory of brain-based learning in developing systemic thinking among seventh grade students in biology through the application of the systemic thinking test that was built by two researchers for students in the basic stage. The test consisted of 14 items to measure systemic thinking skills. In the application, the researchers followed the experimental approach. The study sample consisted of 60 students who were randomly divided into two groups of experimental and control each consisting of 30 students. The researchers taught the experimental group using the proposed program according to the theory of brain-based learning, while the control group was taught by regular education.